THE EFFECT OF CAKE APPLICATION TOWARD STUDENTS LISTENING SKILL AT ELEVENTH GRADE STUDENTS OF SMAN 10 PANDEGLANGIN IN ACADEMIC YEAR 2025/2026 - Silvia Erliyansah Putri; Ari Fajria Novari; Tatu Munawaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the impact of Cake application on listening competence among eleventh-grade students at SMAN 10 Pandeglang during the 2025/2026 academic year. The primary challenge addressed involves students' difficulties in comprehending English conversations, particularly when encountering diverse accents and rapid speech rates, coupled with limited technological integration in listening instruction. Employing a quasi-experimental design, this quantitative research involved 70 participants divided into two groups: an experimental group (n=35) utilizing Cake application and a control group (n=35) using Elsa application. Data collection employed pre-tests and post-tests consisting of multiple-choice questions derived from audio and video materials. Statistical analysis revealed that the experimental group demonstrated substantially superior performance, with mean scores increasing from 58.03 to 84.54, compared to the control group's improvement from 57.69 to 66.43. Independent samples t-test yielded a t-value of 11.866 (p<0.05), significantly exceeding the critical value of 1.672, thereby confirming the alternative hypothesis. These findings demonstrate that Cake application effectively enhances listening proficiency through authentic materials, interactive features, and flexible accessibility, suggesting its viability as an innovative pedagogical tool for English language instruction.